Air Temperature and Gastroenteritis Among Rohingya Populations in Bangladesh Refugee Camps - Takata, Takuya (Archīum Ateneo, 2025)
Importance The Rohingya displaced population in Bangladesh is the largest stateless population in the world. Infectious diseases, such as gastroenteritis, respiratory infections, and fever, are among the major health problems the Rohingya population has faced. Although associations between gastroenteritis and air temperature have been reported in various regions, no study has yet been carried out among the displaced populations. Objectives To evaluate the association between air temperature and risk of gastroenteritis among the forcibly displaced Rohingya population in refugee camps in Bangladesh. Design, Setting, and Participants In this cross-sectional study, daily time series data derived from facility-based case reports were collected in 2 clinics organized by the UNHCR (United Nations High Commissioner for Refugees) in Kutupalong and Nayapara registered camps from January 1, 2019, to December 31, 2021. Statistical analysis was conducted from April 2023 to September 2024. Exposure Hourly 2-m air temperature from ERA5-Land by the European Centre for Medium-Range Weather Forecasts. Main Outcomes and Measures The daily number of gastroenteritis cases recorded in the camp clinics was the main outcome measure. Nonlinear lagged associations between daily temperature and gastroenteritis cases were modeled using a quasi-Poisson generalized linear model to account for overdispersion coupled with a distributed lag nonlinear model including a maximum 21-day lag. Covariates from the literature were adjusted in the model. Results A total of 33280 gastroenteritis cases (95% among individuals aged ≥5 years; 71% female) were recorded in Kutupalong and 31165 gastroenteritis cases (99% among individuals aged ≥5 years; 67% female) were recorded in Nayapara. Further examination revealed a potential U-shaped curve in Kutupalong with minimum risk temperature (MRT) set at 26 °C. Cumulative relative risk (RR) at the 10th percentile temperature (21.1 °C) was 2.31 (95% CI, 1.18-4.65), while RR at 90th percentile temperature (28.5 °C) was 1.78 (95% CI, 1.24-2.56) relative to MRT. In Nayapara, a nearly linear risk increase was observed with decreasing temperature. Cumulative RR at the 10th percentile temperature (21 °C) was 1.32 (95% CI, 0.78-2.24), while the RR at the 90th percentile temperature (28.3 °C) was 0.75 (95% CI, 0.56-0.99). Lagged effects were delayed in nature. In Kutupalong, cold temperatures (10th percentile) were associated with statistically significant gastroenteritis risks at approximately 15 to 20 days (range: RR, 1.06 [95% CI, 1.00-1.13] to RR, 1.10 [95% CI, 1.00-1.21]). In Nayapara, gastroenteritis risks were correspondingly higher at longer lags (lag, 18 days; RR, 1.05 [95% CI, 1.00-1.10]). Conclusions and Relevance In this cross-sectional study of the Rohingya displaced population in Bangladesh, cold temperatures were associated with an increase in the risk of gastroenteritis. It is important to understand the association of climatic factors with the health of displaced communities, whose population is expected to grow in the future.